(3GdBOGH GdOjfjIs - (3Ydj Hf GdMSjf Hf GdaVd GdWHQSj, CHh GdaVds
(3ChdgG (B:s
(3bGd CJjJ GdUGOb LYaQ Hf eMeO YdjgeG GdSdGe ade CLOg NGdjkG aLdSJ aj ehVY HERGFg s
(3BNQgG (B:s
(3bGd Ydjg GdSdGe jG Hf NajS Ef YdefG TaBA hgOi hQMeI ddeDefjf hdGMhd hdGbhI EdG HGddg GdYdj GdYXje s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(133) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs